Pengembangan Aplikasi Mobile Pengaduan Masyarakat Pada Dinas Perhubungan Kota Malang Menggunakan Fitur Location Based Service Berbasis Android - Fegi Eriyani; Bayu Priyambadha; Heru Nurwarsito (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Public complaints are needed in an agency to find out the success of the work, improve deficiencies and receive advice from the tasks that have been carried out. Public complaints usually occur in the field of facilities and public services, where the sector is handled by the Department of Transportation. The public complaint has not been conveyed properly, making the community confused about who to complain to. So in this study discusses about developing a public complaint application on the Transportation Department of Malang City based on Android to facilitate the public in reporting complaints. This application uses the Location Based Service feature that is used to make it easier to find the location of the reporter. Public complaints application can send proof of complaints that occur such as photos through the smartphone application by taking photos from the camera directly or from the reporter's smartphone gallery. Mobile applications are implemented using the Java programming language while the web for administrators is built using the Laravel Framework. This application is tested using whitebox testing for unit testing and integration testing, blackbox testing for testing validation and usability testing. The test results on the application of public complaints state that this application can run as needed and can be used easily by users by having a 83,75 System Usability Scale score or can be said to be acceptable.